Pengaruh pelatihan Early Warning Score (EWS) terhadap tingkat pengetahuan dokter dan perawat dalam penerapan EWS di Rumah Sakit Laras PT. Prima Medika Nusantara Simalungun - Lubis, Andriamuri Primaputra; Rusda, Muhammad; Wahyuni, Arlinda Sari; Effendy, Elmeida; Amin, Mustafa Mahmud (Politeknik Kesehatan Kemenkes Aceh, 2025)
Background: The Early Warning Score (EWS) is a clinical monitoring system based on vital signs, designed to support early detection of patient deterioration. However, its implementation in hospitals is often hindered by limited knowledge and skills among healthcare professionals. Objective: To evaluate the impact of EWS training on improving doctors' and nurses' knowledge regarding the application of the system at Laras Hospital, PT. Prima Medika Nusantara. Methods: A quasi-experimental pre-post study without a control group was conducted involving 155 participants. The EWS training, delivered through lectures and simulations, was followed by pre- and post-intervention knowledge assessments using a structured questionnaire. Statistical analysis was performed using the Wilcoxon test. Results: The findings demonstrated a significant improvement in knowledge after training (p = 0.00), indicating the effectiveness of the intervention in enhancing clinical readiness among medical staff. Conclusion: EWS training plays a vital role in strengthening the clinical competencies of doctors and nurses. Its routine implementation can serve as a practical strategy to enhance early detection systems and improve patient safety and care quality in hospital settings.